A novel bioinspired mechanism to elucidate the movement flexibility of the honeybee abdomen driven by muscles. (30th January 2022) - Zhang, Yu‐Ling; Yan, Shao‐Ze; Liang, You‐Jian
Abstract: The abdomen of a honeybee is a blueprint for bioinspired mechanical design because of its movement flexibility and compactness. However, the abdominal muscles closely related to the movement flexibility mechanism have not been fully identified, limiting the potential biological advantage of their use in bionic mechanism design. In this study, we reveal the muscle distribution of the complete muscular driving unit in a honeybee abdomen using stereoscopy and scanning electron microscopy, and the muscle distribution was effectively verified using X‐ray tomography. A novel equivalent unit mechanism (EUM) was then proposed and the kinematic analysis indicated that the extension ratio, bending angle, and swing angle of the EUM reached 9.36%, 1.22°, and 4.43°, respectively. The deformation ability of the EUM was consistent with the movement of the abdomen, confirming the movement flexibility. This work may provide a new perspective for distributed bionic mechanism design. Abstract : A novel equivalent unit mechanism inspired by the muscle distribution of honeybee abdomen between two adjacent segments was obtained to effectively elucidate the movement flexibility mechanism of honeybee abdomen such as extension, contraction, bending and swing, and further reveals the deformation mechanism of honeybee abdomen.